2010
DOI: 10.1016/j.jfms.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high definition oscillometric and Doppler ultrasonic devices for measuring blood pressure in anaesthetised cats

Abstract: Indirect blood pressure measurements using high definition oscillometric (HDO) and Doppler devices were compared in 50 anaesthetised client-owned cats presented for various surgical procedures. Sites of cuff placement for Doppler were identified as forelimb and hindlimb and for HDO as forelimb and tail. Oscillometric and Doppler readings were obtained in 90.05% and 100% of attempts, respectively. Both devices enabled precise measurement of systolic arterial pressure (SAP), although the Doppler device gave high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 12 publications
3
30
0
1
Order By: Relevance
“…To overcome these difficulties, a high-definition oscillometric technique has been developed. This method shows limited agreement with measurements obtained by invasive methods in anaesthetised dogs (Seliškar and others 2013) and awake cats (Martel and others 2013), or when using the Doppler technique in anaesthetised cats (Petric and others 2010); however, it is being increasingly used in small animal clinics.…”
Section: Monitoring the Monitormentioning
confidence: 91%
“…To overcome these difficulties, a high-definition oscillometric technique has been developed. This method shows limited agreement with measurements obtained by invasive methods in anaesthetised dogs (Seliškar and others 2013) and awake cats (Martel and others 2013), or when using the Doppler technique in anaesthetised cats (Petric and others 2010); however, it is being increasingly used in small animal clinics.…”
Section: Monitoring the Monitormentioning
confidence: 91%
“…13,14 More studies are needed to evaluate HDO, including studies comparing HDO results with values obtained via direct arterial blood pressure monitoring. These methods are technically easy to use and require relatively inexpensive equipment but are prone to error, include accurate readings of values from 5 to 300 mm Hg and highspeed analysis that allows for measurements at heart rates of up to 500 beats/min and during arrhythmias.…”
Section: Noninvasive Blood Pressure Monitoringmentioning
confidence: 99%
“…In cats, only one evaluation study of HDO has been published at present. 5 This evaluation was performed by comparison of measurements obtained by a Doppler ultrasonic device with direct BP measurements undertaken in anaesthetised animals. The authors concluded that discrepancies between the techniques were achieved.…”
Section: Introductionmentioning
confidence: 99%